Factors related to the level of knowledge about dengue among users of the Chongoyape health center, 2022 - Mendo Aguirre , Maite Kimberly (2025)
Introduction: Dengue is a metaxenic disease that affects all people regardless of age, causing symptoms of fever, headache, retroocular and muscle-joint pain. In the studied area, a high number of people infected by the virus was observed; due to a possible relationship with the insufficient adoption of effective preventive practices and limited knowledge of the disease. Objective: To determine the relationship between sociodemographic factors and the level of dengue knowledge in people attending the Chongoyape health center, 2022. Method: Quantitative research with a correlational cross-sectional design. The population was 500 people served, monthly average of medical consultations. The sample was 194 people sampled by convenience in the waiting room of the health facility. The "knowledge about dengue" questionnaire was used (Aiken's V validity = 1; p = 0.004); and reliability with Kuder-Richadrson (KR20 (0.70). The data were processed and analyzed with the SPSS version 27 program. The principle of anonymity, reliability, fair treatment and voluntary and informed participation was considered. Results: More than 90% of the participants interviewed declared having knowledge about the definition, transmission, complications, treatment of dengue and preventive measures of dengue at home. A significant statistical relationship was identified between knowledge of dengue and the level of study (p <0.001). The other factors analyzed did not show a significant relationship, presenting p values ​​= 0.005. Conclusion: There are crucial information gaps about transmitting mosquitoes and risky household behaviors, and targeted public health educational interventions are urgently needed.